2016
DOI: 10.1080/15548627.2016.1204496
|View full text |Cite
|
Sign up to set email alerts
|

TP53-dependent autophagy links the ATR-CHEK1 axis activation to proinflammatory VEGFA production in human bronchial epithelial cells exposed to fine particulate matter (PM2.5)

Abstract: Epidemiological and clinical studies have increasingly shown that fine particulate matter (PM2.5) is associated with a number of pathological respiratory diseases, such as bronchitis, asthma, and chronic obstructive pulmonary disease, which share the common feature of airway inflammation induced by particle exposure. Thus, understanding how PM2.5 triggers inflammatory responses in the respiratory system is crucial for the study of PM2.5 toxicity. In the current study, we found that exposing human bronchial epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…The detected whether IKKα is required for CHK1/p53 interaction in the arsenite response, HepG2 cells were transfected with IKKα siRNA or the control siRNA, and then reciprocal IPs were performed to detect the changes on CHK1/p53 interaction with or without IKKα expression. Cellular protein preparation and immunoblot assays were performed as described previously 17,18 .…”
Section: Immunoprecipitation and Immunoblot Assaymentioning
confidence: 99%
“…The detected whether IKKα is required for CHK1/p53 interaction in the arsenite response, HepG2 cells were transfected with IKKα siRNA or the control siRNA, and then reciprocal IPs were performed to detect the changes on CHK1/p53 interaction with or without IKKα expression. Cellular protein preparation and immunoblot assays were performed as described previously 17,18 .…”
Section: Immunoprecipitation and Immunoblot Assaymentioning
confidence: 99%
“…Previous research has focused on the epidemiology and toxicology of PM2.5; however, more recent research has investigated the function that PM2.5 serves in the pathogenesis of respiratory diseases. PM2.5-induced epigenetic changes, including microRNA dysregulation (37) and DNA methylation (46), microenvironment alteration (53), cell autophagy and apoptosis (67,68), may result in oncogene activation and tumor suppressor gene inactivation in lung cancer (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, autophagy is able to regulate apoptosis by altering the level and activity of caspase proteins (66). PM2.5 exposure may induce macrophage autophagy and mediate the Src/STAT-3 signaling pathway to increase the expression of VEGF-A, an important pro-angiogenic factor (67). It has also been suggested that the phosphoinositide 3-kinase/Akt/mechanistic target of rapamycin kinase signaling pathway may serve an important function in the autophagy of BEAS-2B cells exposed to PM2.5 (68).…”
Section: Pm25-induced Autophagy and Apoptosismentioning
confidence: 99%
“…Exposing human bronchial epithelial cells to high levels of particulate matter 2.5 (PM2.5; the mass per cubic meter of air of particles with a size of less than 2.5 μm) induces significant upregulation of vascular endothelial growth factor A (VEGA) production. Macroautophagy/autophagy is induced upon PM2.5 exposure and then mediates VEGA upregulation by activating the SRC‐CTA3 pathway in bronchial epithelial cells…”
Section: The Link Between Copd and Lung Cancermentioning
confidence: 99%